(untitled) (Bangladesh Journal of Child Health, 2010)
Background: Liver biopsy is an established procedure to diagnose disease, to assess prognosis and to follow up of liver diseases. Although liver biopsy is a confirmatory diagnostic procedure of majority of the hepatological disorders, it carries the risk of complications. Though major complications rarely occur, minor complications are common. To minimize complications, several biopsy techniques have been developed. The present study was intended to correlate the clinical diagnoses with histological diagnoses and to observe the complications encountered by the children with percutaneous liver biopsy procedure. Patients and Methods: A total of 30 paediatric patients of suspected liver diseases, based on predefined eligibility criteria, were subjected to biopsy for confirmation of diagnosis. An ultrasound of liver was routinely performed before the procedure to mark the site for percutaneous biopsy. The field was prepared with alcohol-based solution (povidone-iodine) and sterile drapes were placed over the patient. Local anaesthetic was administered with 2% lidocain solution 20mg/ml (preferably levobupivacaine 2.5mg/ ml) in both superficial and deep planes. A blind liver biopsy was done at the point of maximum dullness by percussion over the right trunk. We used cutting needle. The diameter of the needle used in our study was 14-gauge (1.4 mm) which allowed adequate collection of tissue for diagnosis. The biopsy material was taken in a very small amount of sterile normal saline and was immediately sent to the laboratory for evaluation. Results: Half (50%) of the patients was more than 5 years of age with median age being 5.0±3.9 years. Majority (80%) was male. Ninety percent of the patients belonged to poor socioeconomic class. Clinically the cases were diagnosed as having chronic hepatitis (23.3%) followed by CLD (16.7%), isolated hepatomegaly (16.7%), liver cirrhosis (13.3%) and storage disease (13.3%). Hepatosplenomegaly and congenital hepatic fibrosis, each was 6.7%. Histological diagnoses of biopsy material obtained from the liver confirmed that one-sixth (16.7%) of the cases had liver cirrhosis. Storage disease and glycogen storage disease each comprised 13.3% of the cases and congenital biliary atresia 10%. Very few cases had moderate fatty changes with cholestasis, congenital hepatic fibrosis, chronic inflammatory cells, chronic viral hepatitis and secondary biliary cirrhosis. Nearly half (46.7%) patients had mild pain and discomfort at the site of biopsy, most of which spontaneously went away. However, some 3 (10%) patients developed major complications needing management. Conclusion: Liver biopsy is a well established procedure in the diagnosis and follow up of liver diseases. But it is not without risk of complications. So, before deciding for a liver biopsy, the indications and risks must be assessed cautiously for each patient. Key words: Percutaneous liver biopsy; clinical diagnoses; histological diagnoses; complications. DOI: 10.3329/bjch.v34i1.5694 Bangladesh Journal of Child Health 2010; Vol.34(1): 1-6